2021
DOI: 10.3389/fmed.2021.784320
|View full text |Cite
|
Sign up to set email alerts
|

Qigong for Muscle Strength and Static Postural Control in Middle-Aged and Older Postmenopausal Women: A Randomized Controlled Trial

Abstract: In the present study, we aimed to determine the effects of a Qigong exercise program on the muscle strength and postural control in middle-aged and older postmenopausal women. This is a randomized clinical trial (https://clinicaltrials.gov/ct2/show/NCT03989453) conducted on 125 women who were initially assigned to either an experimental group (n = 63) that performed a Qigong exercise program for 12 weeks or to a control group (n = 62) that did not receive any intervention. Muscle strength (dynamometer) and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…For example, although many forms of qigong include minimal muscle work, an RCT demonstrated that 12 weeks of qigong was associated with improved muscle strength among postmenopausal women. 106 It is also possible that tai chi/qigong may help overcome fatigue or low motivation to engage in exercise, 107 creating a positive feedback cycle. Similarly, greater physical activity is associated with improved sleep quality, 108 which, as discussed previously, is also associated with improved body composition.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although many forms of qigong include minimal muscle work, an RCT demonstrated that 12 weeks of qigong was associated with improved muscle strength among postmenopausal women. 106 It is also possible that tai chi/qigong may help overcome fatigue or low motivation to engage in exercise, 107 creating a positive feedback cycle. Similarly, greater physical activity is associated with improved sleep quality, 108 which, as discussed previously, is also associated with improved body composition.…”
Section: Physical Activitymentioning
confidence: 99%
“…The exercise component of tai chi/qigong likely impacts body composition not only through direct changes in energy expenditure, but also via interactions with other behavioral and physiological factors believed to influence body composition. For example, although many forms of qigong include minimal muscle work, an RCT demonstrated that 12 weeks of qigong was associated with improved muscle strength among postmenopausal women 106 . It is also possible that tai chi/qigong may help overcome fatigue or low motivation to engage in exercise, 107 creating a positive feedback cycle.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Carcelén-Fraile, et al [30] conducted a randomized clinical trial on 125 Spanish middle-aged and postmenopausal women to determine whether a qigong exercise program would have a beneficial effect on muscle strength and postural control. The program lasted for 12 weeks.…”
Section: Muscle Strength and Posturementioning
confidence: 99%
“…In the West, it is sometimes used in conjunction with mainstream medicine as a supplementary tool to treat symptoms of various diseases and ailments [1][2][3][4][5][6][7][8][9][10]. Numerous studies have found that qigong can aid in the treatment of arthritis [11], back pain [12], cancer [13][14][15][16][17], cognitive impairment [18,19], Covid-19 [20,21], COPD [22], depression and anxiety [23][24][25][26], fatigue [27], hypertension [28,29], muscle strength and posture [30], Parkinson's disease [31,32], stroke [33], and tertiary-care pain management [34].…”
Section: Introductionmentioning
confidence: 99%
“…The health advantages of alternative traditional Chinese exercise (TCE) such as Tai Chi and Qigong (Baduanjin) are becoming increasingly popular. Tai Chi and Qigong (Baduanjin) currently have the most substantial evidence of efficacy available, particularly in the improvement of muscle strength, aerobic capacity, and postural stability (Field, 2011;Carcelén-Fraile et al, 2021;Yuen et al, 2021). These are low-cost, mild-to-moderate-intensity workouts that emphasize physical-mental link training with slow, gentle, and symmetrical motions, a meditative state, and breathing control that must be linked with gradual body activity (Wang et al, 2015;Song et al, 2017;Zou et al, 2018a,b;Fidan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%